Cyprus – Bridge or Bunker? / The Cyprus Problem and Prospects for its Resolution - Güven - Lisaniler, Fatma; Warner, Jonathan (Perceptions: Journal of International Affairs / Center for Strategic Research of the Ministry of Foreign Affairs of the Republic of Turkey (SAM), 1998)
[Abstract Not Available]
Keywords: Cyprus Problem - Cyprus Conlict; Cyprus - International Law